Idol Worship Culture of Odisha and Dalit Poet Śāralādāsa - Harekrushna Mishra (Lakhomi Journal Scientific Journal of Culture, 2022)
This research paper is a keen observation of Odia Mahabharat which is commonly known as Saralamahabharata. It is a very interesting fact that a vast monograph with several novelties, this Mahabharat was authored by a Dalit poet of Odisha. He has depicted Jagannatha the Mass deity of Odisha as lord Krishna and tried to establish the inseparability within. His in-depth study and understanding of the mythologies indiscriminately establish the accessibility of each caste to the spectrum of knowledge and knowledge systems as well. His association with Jagannatyha Culture as well as with the Vaisnavite system and the famous Sanskrit epic Mahabharat confirms the association of each segment of Indian Social Order in each aspect of social and cultural life.